2011
DOI: 10.1002/nur.20430
|View full text |Cite
|
Sign up to set email alerts
|

Family caregivers of hospitalized adults in Israel: A point‐prevalence survey and exploration of tasks and motives

Abstract: The prevalence of family inpatient caregiving in Israel, its extent, content, and related caregiver and patient variables were examined. Of 1,076 patients surveyed, 744 (69%) had family caregivers, and 513 caregivers were interviewed. Caregivers averaged 8  hours a day at the hospital and most frequently carried out monitoring tasks. Their main motivation was the desire to help the patient. Variables that explained overall caregiving tasks were the desire to help the patient (β = .38), to ensure quality of car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 45 publications
3
31
0
4
Order By: Relevance
“…This way of thinking, by extension, leads us to believe that including more FCG–hospital staff interaction would strengthen the empowerment aspect of the CARE intervention by allowing introduction of selected nuances to the educational‐behavioral portions. Auslander (2011) encouraged healthcare providers to determine what family members want to do for hospitalized relatives and to identify appropriate tasks that will benefit themselves, patients, and hospital staff.…”
Section: Discussionmentioning
confidence: 99%
“…This way of thinking, by extension, leads us to believe that including more FCG–hospital staff interaction would strengthen the empowerment aspect of the CARE intervention by allowing introduction of selected nuances to the educational‐behavioral portions. Auslander (2011) encouraged healthcare providers to determine what family members want to do for hospitalized relatives and to identify appropriate tasks that will benefit themselves, patients, and hospital staff.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not collect systematic data on this, the population most difficult to reach in our study was the population of family members, who often were not physically present or available for an interview. This is somewhat contrasted with an epidemiological study that found that about 70% of hospitalized Israeli patients were accompanied by a family caregiver (Auslander, 2011). The fact that the study was not age restricted (Auslander, 2011) might explain the apparent discrepancy.…”
Section: Discussionmentioning
confidence: 63%
“…This is somewhat contrasted with an epidemiological study that found that about 70% of hospitalized Israeli patients were accompanied by a family caregiver (Auslander, 2011). The fact that the study was not age restricted (Auslander, 2011) might explain the apparent discrepancy. In addition, in contrast to past research, this study focused on older hospitalized patients who were accompanied by migrant home care workers.…”
Section: Discussionmentioning
confidence: 63%
“…Informal caregivers are usually the significant others in a patient's life, and most patients report that parents, spouses, or adult children accompanied them during hospitalization (Auslander, 2011;Gur-Yaish et al, 2013;Levine et al, 2010).…”
Section: Informal Caregiving Support During Hospitalizationmentioning
confidence: 99%
“…Although hospital staff provide some of this help, informal caregivers who accompany patients during hospitalization provide a substantial portion of it (Auslander, 2011). However, we know little about the effect of the quality of the patient's relationship with his or her informal caregiver and the amount of various types of support received.…”
mentioning
confidence: 99%